A prospective randomized comparative study on fractures of lower third of both bones of the leg treated by interlock nailing of tibia with or without fixation of fibula - Devatheya, Deepak Kumar; Assat, Rajendra Prasad; Dayama, Ratanlal; Meena, Kanta Prasad (International Journal of Research in Orthopaedics, 2017)
Background: In the treatment of fractures of the distal third of tibia and fibula treated by interlocking nail of tibia, the role of fixing the fibular fracture is not clearly defined. This study was conducted to assess the benefits of fixation of fibular fracture in distal third leg bones fractures. Methods: 95 patients were enrolled into study and divided randomly into two groups based on whether fibula fixed or not with interlock intramedullary nailing tibia. Patients were followed for an average period of 11 months both radiologically and clinically. Results: We observed that the average valgus angulation was significantly less (P =0.001) in the group where fibula was fixed. The outcome of the two groups for clinical ankle score, time of union and complication showed no difference (P ≥0.05). Conclusions: We concluded that fixation of fibula decrease the malalignment of tibia in distal third fractures of tibia and fibula treated with interlocking nail of tibia.